2023
DOI: 10.1002/dmrr.3673
|View full text |Cite
|
Sign up to set email alerts
|

Comparison on cognitive outcomes of antidiabetic agents for type 2 diabetes: A systematic review and network meta‐analysis

Sai Tian,
Jiaxuan Jiang,
Jin Wang
et al.

Abstract: We aimed to summarise current evidence on different antidiabetic drugs to delay cognitive impairment, including mild cognitive impairment, dementia, Alzheimer's disease (AD) and vascular dementia, among subjects with type 2 diabetes mellitus (T2DM). Medline, Cochrane and Embase databases were searched from inception to 31 July 2022. Two investigators independently reviewed and screened trials comparing antidiabetic drugs with no antidiabetic drugs, placebo, or other active antidiabetic drugs on cognitive outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 78 publications
(116 reference statements)
0
3
0
Order By: Relevance
“…Studies have reported an association between GLP-1 RA and improved memory and other cognitive functions in animal models [ 17 ]. Potential cognitive benefits also have been observed in individuals with T2DM, treated with GLP-1 RA [ 18 ]. For example, a post-hoc analysis of an RCT with longitudinal follow-up of more than 4 years observed a potential cognitive benefit associated with a type of GLP-1 RA, dulaglutide, in individuals with T2DM [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported an association between GLP-1 RA and improved memory and other cognitive functions in animal models [ 17 ]. Potential cognitive benefits also have been observed in individuals with T2DM, treated with GLP-1 RA [ 18 ]. For example, a post-hoc analysis of an RCT with longitudinal follow-up of more than 4 years observed a potential cognitive benefit associated with a type of GLP-1 RA, dulaglutide, in individuals with T2DM [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study was conducted during a period when newer classes of diabetes medications (eg, sodium-glucose cotransporter 2 inhibitors and glucagon-like peptide 1 receptor agonists) were not frequently prescribed. We were unable to analyze the influence of these specific medications, which may decrease risk of all-cause dementia . We were unable to reliably determine the duration of an individual’s diabetes diagnosis in the electronic health record system.…”
Section: Discussionmentioning
confidence: 99%
“…We were unable to analyze the influence of these specific medications, which may decrease risk of all-cause dementia. 43 We were unable to reliably determine the duration of an individual’s diabetes diagnosis in the electronic health record system. Finally, our results do not show that prospectively maintaining higher HbA 1c TIR as a treatment strategy will reduce risks for ADRD.…”
Section: Discussionmentioning
confidence: 99%